Analisis Sistem Bus USB Dan PCI Pada Organisasi Arsitektur Komputer - Putri Andini Maulana; Muhammad Yusuf Habibi; Agus Gilang Hermawan; Didik Aribowo (International Forum of Researchers and Lecturers, 2023)
Bus systems are an important component of modern computer organization and architecture. In this context, the two types of buses that stand out are Universal Serial Bus (USB) and Peripheral Component Interconnect (PCI). The USB bus is an interface standard commonly used to connect various external devices to a computer, while PCI is an internal bus that connects computer components. This study aims to analyze the role and characteristics of the USB and PCI bus systems in computer organization and architecture. The results of this analysis provide an in-depth understanding of the role of USB and PCI bus systems in modern computer organization and architecture. This information can help IT professionals and system designers make decisions regarding hardware connectivity and performance in a variety of computing environments.